Effects of water injection strategies on performance and exhaust emissions in an ethanol fueled gasoline engine. (1st September 2022) - Cesur, Idris
Highlight: Ethanol and gasoline mixtures are used as an alternative fuel in spark ignition engines. The most effective method among emission reduction methods is water injection. Improvements are observed in engine performance parameters with the water spray method. NOx and HC emissions have been reduced by 28% and 15%, respectively with water injection. Abstract: The increase in the world population and the rapid development of technology cause energy consumption. Alternative fuels to petroleum should be used to meet the increasing energy consumption. In addition, the increase in the use of fossil fuels causes an increase in environmental pollution. Researchers have investigated many methods to reduce pollutant emissions using alternative fuels for internal combustion engines. In this study, alternative fuel and exhaust emission reduction methods were used simultaneously. Firstly, alternative fuel E15 (85% gasoline + 15% ethanol) was used in the engine and emission values were slightly reduced. Secondly, different mass rates (10%, 20% and 30%) of water were injected into the intake manifold to reduce the released emissions further. Using these two methods, reductions in exhaust emissions were determined without any deterioration in engine performance parameters. As a result of the experimental study, the best results in effective power and engine torque were obtained in 20% water injection. The rate of increase compared to the standard engine in the effective powe is 2.5% at 3400 rpm. The maximum amount of reduction in HC emissions was obtained in 20% water injection, and the amount of reduction was 15.3% at 2200 rpm. According to the standard engine data, the maximum reduction in NOx emissions is 28.9% at 3000 rpm. In the study result, it has been found that using alternative fuel and water injection management together improves engine performance and significantly lowers exhaust emissions.